2007
DOI: 10.1007/s10495-007-0145-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism of Mitomycin C-dependent caspase-8 regulation: implications for apoptosis and synergism with interferon-α signalling

Abstract: Caspase-8 is frequently mutated or silenced in several tumors including hepatocellular carcinomas (HCC) thereby potentially contributing to chemoresistance. The aim of our present study was to evaluate if chemotherapeutic drugs may mediate their effects through up-regulation of caspase-8 gene transcription. Huh7 hepatoma cells were transfected with a caspase-8 promoter construct fused to a luciferase reporter gene followed by stimulation with a subset of different chemotherapeutic drugs. Several drugs slightly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 44 publications
1
12
0
Order By: Relevance
“…Our study was in concordance with the studies by Fanini et al . and Shi et al ,29, 30 and we also found that exogenous overexpression of miR‐181b sensitizes SGC7901/VCR and A549/CDDP cells to VCR‐ and CDDP‐induced apoptosis, respectively, and except for VCR and CDDP, exogenous overexpression of miR‐181b also altered sensitivity of both SGC7901/VCR and A549/CDDP cells to ADR, VP‐16, 5‐Fu, but not to MMC, a possible explanation for this phenomenon could be that MMC triggers apoptosis of cancer cells via a pathway where BCL2 is not necessarily involved 32–34…”
Section: Discussionsupporting
confidence: 66%
“…Our study was in concordance with the studies by Fanini et al . and Shi et al ,29, 30 and we also found that exogenous overexpression of miR‐181b sensitizes SGC7901/VCR and A549/CDDP cells to VCR‐ and CDDP‐induced apoptosis, respectively, and except for VCR and CDDP, exogenous overexpression of miR‐181b also altered sensitivity of both SGC7901/VCR and A549/CDDP cells to ADR, VP‐16, 5‐Fu, but not to MMC, a possible explanation for this phenomenon could be that MMC triggers apoptosis of cancer cells via a pathway where BCL2 is not necessarily involved 32–34…”
Section: Discussionsupporting
confidence: 66%
“…Of note, such a phenomenon was observed in PC-3 cells, in which JNK activation appears to be upstream of caspase 8 (38). In support of this conclusion, it has been recently shown that caspase 8 promoter has a c-Jun/AP1 regulatory site, which controls transcription in response to mitomycin C in Huh7 hepatoma cells (41). …”
Section: Discussionmentioning
confidence: 83%
“…Alternatively, apoptosis was determined by quantification of specific caspase-3 enzyme activity (fluorescence units/ μ g protein) in protein lysates from cultured cells as described recently. 33 In brief, protein lysates were incubated with the artificial substrate AFC-DEVD (Enzo Life Sciences, Farmingdale, NY, USA) and the caspase-3 mediated release of AFC from DEVD was quantified by UV spectrometry. For determination of cleaved caspase-3 activity in whole-cell extracts of isolated primary hepatocytes and livers, murine Hepa1-6 hepatoma cells were treated with 50  μ m Sorafenib for 24 h and were used as a positive control (pos.…”
Section: Methodsmentioning
confidence: 99%